Low-cost solid catalyst derived from waste Cyrtopleura costata (Angel Wing Shell) for biodiesel production using microalgae oil - Osman, Nur Syazwani; Rashid, Umer; Yap, Taufiq Yun Hin (Elsevier, 2015)
In the present work, Cyrtopleura costata (Angel Wing Shell) is used for the first time to synthesis of CaO. The produced CaO was utilized as a catalyst for biodiesel production from microalgae Nannochloropsis oculata oil. The Angel Wing Shell (AWS) was calcined at 800 °C and 900 °C for 2 h to convert CaCO3 to activate metal oxide phase. The synthesized catalysts were characterized by using Thermogravimetric analysis (TGA), X-ray diffraction (XRD), Temperature programmed desorption of CO2 (CO2-TPD), BET surface area and Scanning electron microscopy (SEM) analysis. The calcined Angel Wing Shell at 900 °C (CAWS 900) was chosen as the best catalyst due to its high basicity and surface area. This also corresponded to optimization condition where, CAWS 900 showed highest FAME yield (84.11%) at oil to methanol molar ratio 1:150 and catalyst loading of 9 wt.% in 1 h reaction time. The CAWS 900 catalyst also can be reused more than three times with FAME yield greater than 65%. Overall, AWS appears to be an acceptable solid catalyst to convert microalgae oil to biodiesel.